Analysis Geoestatics Multivariate for identification of gold anomaly, Ayahuanca – Puno - Chuquiruna Chávez, Wilder (2018)
The investigation work has analyzed the efficiency of geostatistical tools in surface geochemical samples of rock to determine geochemical anomalies of gold. A total of 5799 samples were evaluated, with an analysis of 53 elements by the atomic absorption spectrometry method; the present work a geostatistical analysis was carried out mainly for Cu, Pb, Zn, As, Ba and Au. This determined the spatial distribution of the gold anomalies, simple and crossed variograms were calculated in the direction of the anisotropy.